UMTS uplink simulator - Vladimir Wieser; Tomas Marek (Communications - Scientific letters of the University of Zilina, 2004)
This paper presents the link level simulator developed at the Telecommunication Department of the University of Žilina. The simulator was developed as part of the project VEGA No. 1/0140/03 “Effective radio resources management methods in next generations of mobile communication networks” and it will be used in the more complex radio interface simulator of the next generation of mobile communication network built at our department. Students studying some problems about spread spectrum methods will also use the simulation model in some subjects, e.g. Digital communications, Mobile Radio Networks.The simulator was developed in MATLAB Simulink and is made on a block principle, which allows adapting and configuring the model as necessary.In this contribution we present the model solution and some simulation results in an uplink direction. The intention of the contribution is not to present new and original results (similar simulators were previously developed in many institutions [1,2]), but to give an overview what will be realized at our department in the field of mobile communication networks.